2023
DOI: 10.3390/foods12051113
|View full text |Cite
|
Sign up to set email alerts
|

Using TRIS-Buffered Plasma-Activated Water to Reduce Pathogenic Microorganisms on Poultry Carcasses with Evaluation of Physicochemical and Sensory Parameters

Abstract: Foodborne diseases are mainly caused by the contamination of meat or meat products with pathogenic microorganisms. In this study, we first investigated the in vitro application of TRIS-buffered plasma-activated water (Tb-PAW) on Campylobacter (C.) jejuni and Escherichia (E.) coli, with a reduction of approx. 4.20 ± 0.68 and 5.12 ± 0.46 log10 CFU/mL. Furthermore, chicken and duck thighs (inoculated with C. jejuni or E. coli) and breasts (with natural microflora) with skin were sprayed with Tb-PAW. Samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Written informed consent was obtained from all participants. (3) Air Samples: BioSamplers KIT (225-9595, SKC, Eighty Four, PA) were installed at approximately 1.5 meters above floor at the ventilation points in the slaughter area, pre-slaughter area, and caged area (3 sampling points in total). Using 0.5% BSA-PBS buffer at a flow rate of 8 mL/h, sampling was conducted for 12 hours per day at 110V.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Written informed consent was obtained from all participants. (3) Air Samples: BioSamplers KIT (225-9595, SKC, Eighty Four, PA) were installed at approximately 1.5 meters above floor at the ventilation points in the slaughter area, pre-slaughter area, and caged area (3 sampling points in total). Using 0.5% BSA-PBS buffer at a flow rate of 8 mL/h, sampling was conducted for 12 hours per day at 110V.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Combined nasal swab samples from 20 frontline slaughterhouse workers into one pool. (3) Combined air samples collected continuously for 3 days from each sampling point, creating one pool per sampling point. (4) Combined soil samples collected from each space (mixed samples with four or more points) into one pool.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grosse‐Peclum et al. (2023) reported that PAW caused slight differences in pH, color, and myoglobin redox forms when it interacted with chicken carcass, but these differences were not perceived during the sensory analysis.…”
Section: Applications Of Paw For Meats and Meat Productsmentioning
confidence: 99%
“…They are also key points for the transmission of pathogenic microorganisms ( Benfu et al, 2021 ). Due to the high density and mobility of poultry when entering the market or slaughterhouses, poultry comes from diverse sources and has varying hygienic conditions, and may carry multiple pathogenic microorganisms ( Große-Peclum et al, 2023 ). The slaughter process is prone to contaminating the environment and the personnel involved.…”
Section: Introductionmentioning
confidence: 99%